SEX PHEROMONE AND PATTERN OF MATING COMMUNICATION OF FIREFLIES IN SUBFAMILY LAMPYRINAE (COLEOPTERA: LAMPYRIDAE) - Wattanachaiyingcharoen, Wandee; Phanmuangma, Winyoo; Boonphong, Surat; Suphrom, Nungruthai; Prasanpan, Surisak (PSRU Journal of Science and Technology, 2020)
Fireflies in the subfamily Lampyrinae are recognized as glow-worms because they emit continuous green light for sexual communication. Many reports revealed that those glow-worms combined continuous glow with chemical secretion in mating encounters. Four species of fireflies including Diaphanes sp.1, Diaphanes sp.2, Pyrocoelia praetexta and Lamprigera tenebrosa, were investigate their specific pattern of mating communication. The chemical secretions from female fireflies were collected during their mating time to determine the chemical components using GC-MS analysis. Also, we observed the morphological characters related to mating behavior. The sex pheromones of Diaphanes sp.1 and Diaphanes sp.2 consisted of six chemical components (hydrocarbons) with four similar chemicals; tetracosane, pentacosane, hexacosane and heptacosane. However, the sex pheromone from P. praetexta comprised of only one unidentified chemical whereas L. tenebrosa showed no detection of any chemicals. These results indicated that these firefly species used a specific chemical clue for sexual communication within generic and species levels. The observations of morphological characteristics showed that males in all species, except L. tenebrosa, possess complex antennae, which assist in the chemical communication. The results indicated that fireflies in the subfamily Lampyrinae had a variation in mating communication. The first group communicates by emitting the continuous light combine with sex pheromone (Diahanes sp.1, Diaphanes sp.2 and Pyrocoelia praetexta) and the second group (L. tenebrosa) solely employs brighter glow in sexual communication.